Utilizing the zinc homeostasis system of Escherichia coli as a novel inducible promoter system - Ingram, Joseph (2021)
Zn(ii) is an essential post-transition metal found in all life, however, at high concentrations Zn(ii) can become toxic, causing oxidative stress and inactivation of essential enzymes by replacing other metals in catalytic centres of proteins. Escherichia coli cells can control their internal zinc to a femtomolar concentration, equivalent to one to two free Zn(ii) ions per cell. This tightly controlled zinc homeostasis system is regulated by two transcription factors, ZntR and Zur, which regulated the expression of the major zinc export and zinc acquisition genes. This zinc homeostasis system of E. coli has the potential to be developed as a novel inducible promoter system.